THE EFFECTIVENESS OF USING EDMODO IN ENHANCING STUDENTS’ OUTCOMES IN ADVANCE WRITING COURSE OF THE FIFTH SEMESTER AT FIP - UMMU - Erwin Gay; Nurlaily Sofyan (Journal of English Education, 2017)
The increase of interest in the use of computer-mediated communication (CMC) into students learning and English Language Teaching (ELT) has become a crucial part of a 21st century education. Virtual Learning Environments as a supplementary tool for motivating and empowering independent learning and innovative teaching is practicing to deliver coursework in higher education. Edmodo, called as the “Facebook for Education”, was used to discuss the findings of students’ attitude in writing skill. Data was collected by means of questionnaires, interview, forum discussion, and students’ written evaluation. A mixed method of qualitative and quantitative was used to analyze the students’ perspective about using this online learning tool and the results attained from the assignment feature. The primary instrument, a researcher at Muhammadiyah University of North Maluku (UMMU), worked with a class of fifth semester undergraduate students (approximately 20) of English department of UMMU to introduce Edmodo as online learning is a part of new curriculum practices. The research investigated the effectiveness of using a CMC tool to improve students' writing skill, especially to explore how the use of Edmodo in language learning might contextualize and integrate language instruction using Internet technology. These include relationships with significant social settings, implementation of Edmodo into the curriculum, affective factors, and mastery of metacognitive skills. The results show that the use of Edmodo is successfully facilitating students’ participation in online discussions and task. This also enhanced students’ interest and motivation in improving their writing skill.It reflected that a curriculum and learning activities developed on the basis of sociocultural theory and communicative teaching approach could increase interaction and communication through the SCMC system